Multi-objective optimization problems: method and application - Ismail, Fatimah Sham (IEEE, 2011)
Self organizing genetic algorithm (SOGA) is a class of heuristic multi-objective optimization method that has high capabilities for solving multiple conflicting objective functions. This paper presents an application of SOGA for optimizing multi-objectives components placement of multi voltage regulator (MVR) system on printed circuit board by considering multi-constraint parameters. The simulation results, which are developed based on experimental measurement, show that the SOGA can propose better optimal solution compared to the initial design.